The struggle for Egypt : Saudi Arabia’s regional role - M. Dorsey, James (2014)
Recent events in Egypt and Syria suggest a concerted Saudi effort to contain the wave of calls for change across the Middle East and North Africa. The move has led to the rise of Saudi allies in Egypt and Syria and the adoption of procedures that favour the kingdom and put the Muslim Brotherhood’s main foreign backer, Qatar, under its new emir, on the defensive.